PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGGAH DAN PERHITUNGAN PAJAK TERHADAP PENERAPAN PERATURAN PEMERINTAH NO 23 TAHUN 2018 (Studi Kasus UD Mardi Mulyo Mebel Surakarta) - Aviani Kuryana; Fadjar Harimurti; Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Applicable Financial AccountingnStandards for Micro,nSmall, and Discouraging Entitiesn(SAK EMKM). The standard is used for the preparation of Financial Statements for MSMEs so that the financial statements in MSMEs are well organized and used for decision making. Along with the issuance of SAK EMKM accompanied by changes to the tax law namely Law No.23 of 2018 on Income Tax Article 4 paragraph 2 at a rate of 0.5%. The tax is a compulsory levy paid by the people to the state and will be used for various interests of the government and the general public. The results showed that the recording by UD Mardi Mulyo Furniture was manual which was used to find out the number of goods sold during one sales and purchase cycle, as well as in the payment of employee salaries, so the accounting record procedures performed by UD Mardi Mulyo Furniture were still far from SAK EMKM and UD Mardi Mulyo Furniture has not calculated taxes according to the tariffs based on PP No. 23 of 2018 so that the information obtained from the notes cannot be used fully to support or be useful in making decisions more thoroughly from the operational activities of UD Mardi Mulyo Furniture. The causal factor which becomes an obstacle in preparing financial reports and performing tax calculations is the absence of a clear division of tasks between fields due to lack of knowledge about bookkeeping and taxation. The owner manages his own business, so his time is focused on working on and developing the business. This type of data usesnqualitative and quantitative. The data source uses primary data andnsecondary data. Data analysisntechniques using descriptive analysis.